Pembelajaran Ikatan Molekul Dalam Pelajaran Kimia Menggunakan Augmented Reality - Honoris Setiahadi; Endang Setyati; Esther Irawati Setiawan (Universitas Muhammadiyah Sidoarjo, 2017)
Merging two atoms that have valence electrons around them can be described but it is not an easy thing for high school students in the Natural Sciences (IPA) class. This study analyzes the effectiveness of Android-based Augmented Reality (SMARt) System Molecules technology on understanding molecular bonding material in chemistry lessons. The SMARt technology is able to provide a better understanding of molecular bonding material because there are 3D animation of elements and molecules with valence electrons surrounding it. The post test average value for the control class was 68.57 without using SMARt technology while the experimental class average value was 79.71 after using SMARt.